An inverse problem methodology for multiple parameter estimation in bend stiffeners. (February 2019) - He, Yangye; Vaz, Murilo Augusto; Caire, Marcelo
Highlights: A monitoring approach is proposed to decrease uncertainties associated to bend stiffener mechanical response and effective top tension employed for flexible riser lifetime (re)assessment. The approach consists of gyrometers installed along flexible riser/bend stiffener top connection system length combined with an inverse problem methodology based on the Levenberg–Marquardt algorithm. A large deflection beam bending top connection model is employed considering polyurethane nonlinear elastic response. Abstract: The flexible riser top connection is a critical region for lifetime assessment due to large tension/curvature variations and modeling uncertainties. The bend stiffener polyurethane mechanical response not only presents a nonlinear loading rate and temperature dependency but is also subjected to weather ageing during operation, which may affect its mechanical behavior over time. The top tension, employed for riser local cross-section stress calculation, is usually obtained from global dynamic analyses performed under selected environmental conditions, if direct measurement is not available. As a consequence, both the bend stiffener effect on the curvature distribution and the top tension time series present inherent uncertainties for riser lifetime (re)assessment. In the present work, a proposed monitoring approach composed by gyrometers installed along flexible riser/bend stiffener top connection system length combined with an inverse problem methodology is numerically investigated to estimate the following parameters: (i) polyurethane hyperelastic response and (ii) effective top tension. The top connection system is modeled using a large deflection beam bending model and the parameters are estimated using a damped least-square minimization approach with the Levenberg–Marquardt algorithm. For the preliminary feasibility investigation, the gyrometer experimental data is numerically estimated through Monte Carlo simulations. A case study is carried out to investigate the influence that the number of sensors, sensors arrangement, loading conditions and top connection model have on the inverse parameters estimation. The results indicate that the proposed monitoring approach and inverse parameter estimation methodology may effectively reduce flexible riser lifetime calculation uncertainties.